1987
DOI: 10.1016/s0006-3495(87)83326-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence energy transfer as an indicator of Ca2+-ATPase interactions in sarcoplasmic reticulum

Abstract: Ca2+-ATPase molecules were labeled in intact sarcoplasmic reticulum (SR) vesicles, sequentially with a donor fluorophore, fluorescein-5'-isothiocyanate (FITC), and with an acceptor fluorophore, eosin-5'-isothiocyanate (EITC), each at a mole ratio of 0.25-0.5 mol/mol of ATPase. The resonance energy transfer was determined from the effect of acceptor on the intensity and lifetime of donor fluorescence. Due to structural similarities, the two dyes compete for the same site(s) on the Ca2+-ATPase, and under optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 65 publications
4
20
0
Order By: Relevance
“…In analogy to various biochemical findings [14][15][16][17] and electron microscopical data which suggest an oligomeric structure for the SR Ca2+-ATPase [13], we provide in this report biochemical evidence that this abundant muscle calcium ion pump exists in its native membrane environment as a quaternary structure in a multi-copy complex of 110 kDa units. Previous crosslinking studies of the sarcoplasmic reticulum used protein gels for the analysis of the microsomal 110 kDa protein [18][19][20][21][22].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In analogy to various biochemical findings [14][15][16][17] and electron microscopical data which suggest an oligomeric structure for the SR Ca2+-ATPase [13], we provide in this report biochemical evidence that this abundant muscle calcium ion pump exists in its native membrane environment as a quaternary structure in a multi-copy complex of 110 kDa units. Previous crosslinking studies of the sarcoplasmic reticulum used protein gels for the analysis of the microsomal 110 kDa protein [18][19][20][21][22].…”
Section: Resultssupporting
confidence: 82%
“…In addition, exclusion chromatography of detergent solubilized Ca2+-ATPase preparations [14], fluorescence energy transfer measurements of native and reconstituted membranes [15], kinetic measurements on calcium translocation [16] and radiation inactivation studies of the Ca2+-ATPase [17] all argue in favor of oligomeric SERCA structures. In addition, previous crosslinking studies of SR membranes indicate that a 110 kDa protein exhibits a tendency to form oligomeric forms as reviewed by Andersen [18].…”
Section: Introductionmentioning
confidence: 99%
“…Structural similarities between FITC and EITC suggest that EITC could be attached to the same site, as was observed for the Ca 2 pump of sarcoplasmic reticulum [18]. This binding site is close Fig.…”
Section: Monitoring Pmca Dimerization By Using Fretsupporting
confidence: 61%
“…Labeling of the PMCA with £uorescent probes Ca 2 pump was labeled with either £uorescein-5P-isothiocyanate (FITC) or EITC as described previously [18] with some modi¢cations. CaM-depleted erythrocyte membranes were suspended in a bu¡er composed of: 5 WM CaCl 2 , 15 mM MOPS-K (pH 8.4 at 25³C), 0.1 mM PMSF, 4 mg/ml of protein and either 18 WM of FITC or EITC.…”
Section: +mentioning
confidence: 99%
“…However, Murphy's data and our own results show that the Ca 2ϩ -ATPase affinity for free fluorescein is not particularly high, being strongly increased (at least two orders of magnitude) by the addition of halogenated substitutes to the molecule. Many authors have used eosin isothiocyanate (Papp et al, 1987;Munkonge et al, 1988) and erythrosin isothiocyanate (Papp et al, 1987;Birmachu and Thomas, 1990;Voss et al, 1991) rather than FITC, due to their higher affinity and particular fluorescence characteristics, to study rotational movements of the SR Ca 2ϩ -ATPase. These authors concluded that both compounds bind to the same site and react with the same lysyl residue as FITC (Papp et al, 1987;Birmachu and Thomas, 1990).…”
Section: Discussionmentioning
confidence: 99%